TEACHING NARRATIVE READING BY USING ANNOTATION STRATEGY TO THE TENTH GRADE STUDENTS OF SMA NURUL IMAN PALEMBANG - Syinta Pancarini (Edukasi, 2016)
The objectives of the study are to find out whether or not there is significant improvement on students’ reading comprehension score who are taught by using Annotation Strategy and those who are not to the tenth grade students of SMA Nurul Iman Palembang, and to find out whether or not there is a significant difference on students’ reading comprehension score who are taught by using Annotation Strategy and those who are not to the tenth grade students of SMA Nurul Iman Palembang. This study used quasi-experimental design using nonequivalent pretest-posttest design. In collecting the data, test was used. The test was given twice to experimental and control groups, as a pretest and posttest. To verify the hypotheses, the data of pretest and posttest of the experimental and control groups were analyzed by using independent sample t-test and paired sample t-test in SPSS program.  The findings showed that the p-output from paired sample t-test sig (2-tailed) was 0.000 which was lower than 0.05 and the t-value (9.960) was higher than t-table with df=38 (2.0244). The p-output of independent sample t-test was 0.001 which was lower than 0.05 and the t-value (3.332) was higher than t-table with df=76 (1.9917). It means that teaching narrative reading comprehension by using Annotation Strategy had a significant effects on the students’ reading comprehension achievement.